Problematika dan Strategi Pembelajaran Daring pada Era Pandemi Covid-19 - Arianti, Nila; Sutama, Sutama (JKPD (Jurnal Kajian Pendidikan Dasar), 2024)
Closing the school as one of the policies taken to minimize the spread of corona viruses. The original learning activities are performed directly with face-to-face, now having to turn into online learning. Therefore, there is a need to adjust various parties to implement an online learning scheme. The purpose of this research is to identify the problems faced during the implementation of online learning, while describing appropriate strategies to be implemented so that online learning can run effectively. This type of research is a research study with the object of research that is problematic and online learning strategies in the Covid-19 pandemic era. To determine the validity and validity of data, this research uses source triangulation and extra time. The data analysis technique used is the constant comparison method. The results of the study obtained strategies for applying online learning that are appropriate based on the problem at hand.